Gurus of modern yoga - Singleton, Mark; Goldberg, Ellen S. (Oxford University Press, 2014)
Machine generated contents note: -- Contributors -- Note on Transliteration -- Introduction -- Mark Singleton and Ellen Goldberg -- Part One: Key Figures in Early Twentieth-Century Yoga -- Chapter 1: Manufacturing Yogis: Swami Vivekananda as a Yoga Teacher -- Dermot Killingley -- Chapter 2: Remembering Sri Aurobindo and the Mother: The Forgotten Lineage of Integral Yoga -- Ann Gleig and Charles I. Flores -- Chapter 3: Shri Yogendra: Magic, Modernity and the Burden of the Middle-Class Yogi -- Joseph S. Alter -- Part Two: The Lineages of T. Krishnamacharya -- Chapter 4: T. Krishnamacharya, ''Father of Modern Yoga'' -- Mark Singleton and Tara Fraser -- Chapter 5: ''Authorized by Sri K. Pattabhi Jois'': The Role of Parampara and Lineage in Ashtanga Vinyasa Yoga -- Jean Byrne -- Chapter 6: B.K.S. Iyengar as a Yoga Teacher and Yoga Guru -- Frederick M. Smith and Joan White -- Chapter 7: The Institutionalization of the Yoga Tradition: ''Gurus'' B. K. S. Iyengar and Yogini Sunita in Britain -- Suzanne Newcombe -- Part Three: Tantra Based Gurus -- Chapter 8: Swami Krpalvananda: The Man Behind Kripalu Yoga -- Ellen Goldberg -- Chapter 9: Muktananda: Entrepreneurial Godman, Tantric Hero -- Andrea R. Jain -- Chapter 10: Stretching toward the Sacred: John Friend and Anusara Yoga -- Lola Williamson -- Part Four: Bhaktiyoga -- Chapter 11: Svaminarayana: Bhaktiyoga and the Aksarabhraman Guru -- Hanna H. Kim -- Chapter 12: Sathya Sai Baba and the Repertoire of Yoga -- Smriti Srinivas -- Part Five: Technology -- Chapter 13: Engineering an Artful Practice: On Jaggi Vasudev's ISHA Yoga and Sri Sri Ravi Shakar's Art of Living -- Joanne Punzo Waghorne -- Chapter 14: Online Bhakti in a Modern Guru Organization -- Maya Warrier -- Part Six: Nation-Builders -- Chapter 15: Eknath Ranade, Gurus and Jivanvratis (life-workers): Vivekananda Kendra's Promotion of the ''Yoga Way of Life'' -- Gwilym Beckerlegge -- Chapter 16: Swami Ramdev: Modern Yoga Revolutionary -- Stuart Sarbacker -- Index